Compartmentalized expression of two structurally and functionally distinct 4-coumarate:CoA ligase genes in aspen (Populus tremuloides) - Hu, Wen-Jing (The National Academy of Sciences, 1998)
4-Coumarate:CoA ligases (4CLs, EC 6.2.1.12) are a group of enzymes necessary for maintaining a continuous metabolic flux for the biosynthesis of plant phenylpropanoids, such as lignin and flavonoids, that are essential to the survival of plants. So far, various biochemical and molecular studies of plant 4CLs seem to suggest that 4CL isoforms in plants are functionally indistinguishable in mediating the biosynthesis of these phenolics. However, we have discovered two functionally and structurally distinct 4CL genes, Pt4CL1 and Pt4CL2 (63% protein sequence identity), that are differentially expressed in aspen (Populus tremuloides). The Escherichia coli-expressed and purified Pt4CL1 and Pt4CL2 proteins exhibited highly divergent substrate preference as well as specificity that reveal the association of Pt4CL1 with the biosynthesis of guaiacyl–syringyl lignin and the involvement of Pt4CL2 with other phenylpropanoid formation. Northern hybridization analysis demonstrated that Pt4CL1 mRNA is specifically expressed in lignifying xylem tissues and Pt4CL2 mRNA is specifically expressed in epidermal layers in the stem and the leaf, consistent with the promoter activities of Pt4CL1 and Pt4CL2 genes based on the heterologous promoter-β-glucouronidase fusion analysis. Thus, the expression of Pt4CL1 and Pt4CL2 genes is compartmentalized to regulate the differential formation of phenylpropanoids that confer different physiological functions in aspen; Pt4CL1 is devoted to lignin biosynthesis in developing xylem tissues, whereas Pt4CL2 is involved in the biosynthesis of other phenolics, such as flavonoids, in epidermal cells.